Door to needle time and functional outcome for mild ischemic stroke over telestroke. (July 2019) - Harvey, Jillian; Al Kasab, Sami; Almallouhi, Eyad; Guerrero, Waldo R; Debenham, Ellen; Turner, Nancy; Aysse, Patricia; Holmstedt, Christine A
Introduction: Faster intravenous alteplase (tPA) administration from time of symptom onset is associated with better functional outcome. Lack of recognition of mild ischemic stroke (MIS) might result in delay in treatment with tPA. We hypothesise that patients with MIS have a longer door to needle (DTN) time when compared to patients with severe stroke symptoms. Methods: Data on all patients who received tPA at spoke hospitals through the Medical University of South Carolina (MUSC) telestroke network were analysed. Collected data included baseline characteristics, stroke severity on presentation measured by the National Institute of Health Stroke Scale (NIHSS), the rate of symptomatic intracerebral haemorrhage, discharge location, and discharge functional outcome measured by the modified Rankin scale. Results and Discussion: Of the 454 patients treated with tPA through the MUSC telestroke network in the period from January 2013 to April 2017, 98 (22%) had MIS defined as NIHSS ≤ 5 on presentation; the remaining 356 (78%) patients were found to have severe stroke defined as NIHSS > 5 on presentation. Patients presenting with MIS were found to have a delay in receiving intravenous tPA by ∼10 min ( p  = 0.007) and approximately 15% of them had poor functional outcome at discharge. Patients with a MIS on presentation have significantly more prolonged DTN time. Nearly 15% of low severity strokes had poor outcome even after receiving tPA.